(untitled) (World Bulletin of Management and Law, 2025)
This article describes the changes in the global financial architecture in the context of globalization and current trends in the development of the international financial system, as well as the international movement of capital and the dynamics of the global currency market. The article formulates the author’s concept of creating a crisis-resistant global financial architecture, which includes two stages. At the first stage, it is necessary to resolve all the key problems of stabilization and post-crisis development of the global financial architecture in the short and medium term. The second stage of its restructuring includes a direct transformation of the global financial architecture in the context of a change in the financial and economic paradigm (neoliberal doctrine) and the establishment of a new world order - a more active movement towards multipolarity, taking into account the interests of "growing markets". New directions and dominants of the institutional formation of the world financial architecture are investigated. According to the candidate’s assessment, in addition to the rather effective activities of the Financial Stability Council, it is advisable to create another international regulatory body for the financial sector, as well as to organize a new international institution to monitor and research financial and capital markets, within which the function of ensuring cooperation may be required national regulators, uniform standards of information disclosure by issuers, behavior of market participants, bidding procedures, accounting rules, risk assessment.